2006
DOI: 10.1103/physreva.73.042708
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-Rayleigh light-scattering spectra determined byab initiocollisional hyperpolarizabilities ofHeNeatomic pairs

Abstract: The collision-induced ͑CI͒ first hyperpolarizability tensor for the He-Ne pair composed of the lightest noble gas elements has been obtained on the grounds of an ab initio method as a function of the interatomic distance R. Collision-induced hyper-Rayleigh ͑CIHR͒ spectra scattered in mixtures of such atoms at temperatures of 95 and 295 K are computed in absolute units both quantum mechanically and classically for the frequency shifts up to 1000 cm −1 . The spectral features of the CIHR profiles due to the vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…We single out a few significant papers related to the above field. Głaz et al [71] reported a study of the collision-induced hyper-Rayleigh light-scattering spectra of He-Ne atomic pairs. Chrysos et al [72] reported a study of the CO 2 -Ar collision-induced n 3 CO 2 band.…”
Section: Interaction-induced Electric Propertiesmentioning
confidence: 99%
“…We single out a few significant papers related to the above field. Głaz et al [71] reported a study of the collision-induced hyper-Rayleigh light-scattering spectra of He-Ne atomic pairs. Chrysos et al [72] reported a study of the CO 2 -Ar collision-induced n 3 CO 2 band.…”
Section: Interaction-induced Electric Propertiesmentioning
confidence: 99%
“…Indeed, light losses due to the experimental optical setup can be important and, at least, we must consider the upper order of magnitude to be 10 −82 cm 8 s erg −1 . However, this shows that the HR spectra recently studied by our group in a purely theoretical way could be scanned experimentally in a wide frequency range relative to the central frequency 2ν L [14][15][16][17]. This would offer the possibility of extracting from the spectra crucial information about the symmetry-adapted components, as we will see further in the case here considered, H 2 -Ne.…”
Section: Experimental Remarksmentioning
confidence: 71%
“…The blueprint for the presented study has four major steps following the footprints of our previous works: quantum chemistry (QC) ab initio calculations of the hyperpolarizability properties of the compound considered, evaluation of the symmetry-adapted components of the hyperpolarizability tensor and their fitted dependencies on the intermolecular distance R, translational spectral contribution computations, and finally, determination of the resulting full rototranslational lines of CIHR spectra [14][15][16][17][18][19].…”
Section: Spectral Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction hyperpolarisability of He 2 , Ne 2 , and He 3 was discussed using an ab initio wave function, McWeeny's coupled Hartree-Fock perturbation theory and an efficient algorithm [8]. Furthermore, collision-induced hyper-Rayleigh spectra of Ne-Ar [9], He-Ne [10], and He-Ar [11] were computed, and the spectral features were discussed. The application of conventional generalized gradient approximation (GGA) and meta-GGA density functionals to van der Waals interactions is fraught with difficulties, and the PW86 exchange, combined with a dynamical correlation GGA and the Becke-Johnson dispersion model, yielded excellent results in noble gas diatomics [12].…”
Section: Introductionmentioning
confidence: 99%